The Influence of Employees’ Knowledge as a Moderator on the Relationship Between Total Productive Maintenance and Production Efficiency: A Case Study of Auto Parts Manufacturing Company in Chonburi Province - Klahan , Boonta; Laohavichien, Tipparat (KKBS Journal of Business Administration and Accountancy, 2022)
This research aimed to study the influence of total productive maintenance (TPM) on production efficiency and employee knowledge as a moderator on the relationship between the total productive maintenance and production efficiency of a case study company. A case study company is an auto parts manufacturing company in Chonburi Province. The respondents of this study were 296 staff in the production and maintenance department, and collected data by questionnaire. Statistical Techniques used to test the hypotheses were Pearson’s correlation coefficient analysis and multiple regression analysis. The results were interpreted at 0.05 statistically significant levels. The results of this study are as follows: most of the respondents show a high level of total productive maintenance knowledge, and they frequently participate in TPM activities; TPM shows positive related to production efficiency, TPM activities in the dimension of focused improvement, autonomous maintenance, quality maintenance, office improvement and safety health and environment management have an effect on the production efficiency, and employee knowledge of TPM does not act as a moderator in the relationship between the TPM and production efficiency. The results of this study could be applied as the guidelines in TPM planning or TPM improvement for other organizations that need to implement TPM to increase the production efficiency of their companies.